E-Receipt Based Value Added Tax Accounting Treatment at CV Mega Lestari Manado - WALAKANDOU, Olivia Gracia; SONDAKH, Jullie Jeanette; BUDIARSO, Novi Swandari (PT Keberlanjutan Strategis Indonesia, 2023)
The purpose of this study was to determine how the accounting treatment of value added tax based on e-invoice. This study uses a qualitative method with a descriptive approach and the focus in this research is the application of VAT, calculation of VAT, recording of Output and Input VAT, reporting of VAT tax invoices, and the implementation of the e-invoicing system at CV Mega Lestari. The results of this study are CV Mega Lestari has calculated and recorded VAT in accordance with the applicable Taxation Law but in terms of VAT reporting it is not appropriate because the tax reporting is still not timely, and for VAT reporting using the e-invoice application is more efficient. and make the job easier. From the results of data analysis and discussion, it will be concluded that the accounting treatment of CV Mega Lestari's value added tax has carried out its rights and obligations in accordance with the Value Added Tax Law no. 42 of 2009 in terms of calculation and recording. In terms of reporting, the company should increase knowledge about tax regulations, especially regarding the making of tax invoices to avoid delays in reporting so that the company is not subject to sanctions. And related to the use of e-invoicing applications, it must be further improved to minimize the occurrence of errors.